Baropodometric analyses of patients before and after bariatric surgery - Ivan Leo Bacha; Fernanda Antico Benetti; Júlia Maria D’Andréa Greve (Clinics, 2015)
OBJECTIVE: The aim of this study was to evaluate the vertical component of the ground reaction force, plantar pressure, contact area of the feet and double-support time using static and dynamic (gait) baropodometry before and after bariatric surgery. METHODS: Sixteen individuals with a body mass index of between 35 and 55 were evaluated before and after bariatric surgery. Thirteen patients (81.3%) were female and three (18.8%) male and their average age was 46±10 (21-60) years. An FSCAN system (version 3848) was used for baropodometric analyses (1 km/h and 3 km/h). The peak plantar pressure and ground reaction force were measured for the rear foot and forefoot. The double-support time and foot contact area were measured during gait. RESULTS: There were reductions in the ground reaction force in the forefoot and rear foot and in the foot contact area in all evaluations and of the double-support time at 3 km/h, as well as a significant reduction in the body mass index at six months post-surgery. The peak pressure did not vary at 1 km/h and at 3 km/h, reductions in peak pressure were observed in the left and right rear feet and left forefoot. CONCLUSIONS: Weight loss after bariatric surgery resulted in decreases in the ground reaction force and contact area of the foot. Plantar pressure was decreased at 3 km/h, especially in the forefoot. There was an increase in rhythm because of a reduction in the double-support time at 3 km/h.